2014
DOI: 10.1002/2014wr015462
|View full text |Cite|
|
Sign up to set email alerts
|

Reliable probabilistic forecasts from an ensemble reservoir inflow forecasting system

Abstract: This paper describes a probabilistic reservoir inflow forecasting system that explicitly attempts to sample from major sources of uncertainty in the modeling chain. Uncertainty in hydrologic forecasts arises due to errors in the hydrologic models themselves, their parameterizations, and in the initial and boundary conditions (e.g., meteorological observations or forecasts) used to drive the forecasts. The Member-to-Member (M2M) ensemble presented herein uses individual members of a numerical weather model ense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 67 publications
(129 reference statements)
1
18
0
Order By: Relevance
“…The Continuous Ranked Probability Score (CRPS) is a widely used tool for the probabilistic forecast verification [47]. The CRPS might be considered as the mean absolute error of the predicted ensemble, with a lower CRPS value indicating a higher forecasting accuracy.…”
Section: Prediction Evaluationmentioning
confidence: 99%
“…The Continuous Ranked Probability Score (CRPS) is a widely used tool for the probabilistic forecast verification [47]. The CRPS might be considered as the mean absolute error of the predicted ensemble, with a lower CRPS value indicating a higher forecasting accuracy.…”
Section: Prediction Evaluationmentioning
confidence: 99%
“…Despite the great progress and breakthroughs in research on water information telemetry, radar rainfall measurement technology and hydrological models, hydrological forecasting has always been accompanied by inherent uncertainty (Moges et al, 2020). In order to quantify the uncertainty of hydrological forecasts, a large amount of research work has been carried out by scholars worldwide in the last years, and many effective theoretical methods have been proposed (Ajami et al, 2007;Beven and Freer, 2001;Bourdin et al, 2014;Ghaith and Li, 2020). According to the form of forecast release, hydrological forecasts can be divided into three categories: deterministic forecasts, probabilistic forecasts and ensemble forecasts (Cloke and Pappenberger, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the uncertainty in the FODM chain has attracted much attention from academia, and great progress has been made in hydrology and water resources management. The first advance was the development of ensemble flood forecasts (see the review by Cloke & Pappenberger, 2009), shown to be an effective way of quantifying forecast uncertainty (Beven & Freer, 2001;Bourdin et al, 2014;Krzysztofowicz, 1999). However, gaps still exist between theory and application, and more efforts should be directed toward incorporating this type of forecast into water resources operations (Cloke & Pappenberger, 2009).…”
Section: Introductionmentioning
confidence: 99%